A multi-scale investigation of movement patterns among black-tailed prairie dog colonies - Pigg, Rachel M. (Kansas State University, 2014)
Dispersal remains one of the most important, yet least understood, life history traits. As the vehicle of gene flow among populations, dispersal can both relieve inbreeding depression and prevent local adaptation. Regionally, dispersal can stabilize or destabilize metapopulations, given its critical roles in disease transmission among populations as well as recolonization following local extinction events. Furthermore, in light of climate change and increasing habitat loss and fragmentation, the ability to navigate through unfamiliar, unsuitable habitat between populations is essential to the long-term survival of a species across its range. In my dissertation, I present a multi-scale investigation of factors affecting gene flow and disease transmission among populations of a keystone species and an agricultural pest of the North American prairie: the black-tailed prairie dog (Cynomys ludovicianus). Black-tailed prairie dogs are social, ground-dwelling squirrels that live in spatially isolated populations called colonies. First, we conducted a landscape genetic analysis of black-tailed prairie dogs throughout a large portion of their current range. Our estimates of gene flow indicate that the genetic neighborhood size of both male and female prairie dogs reaches 40-60 km within short-grass prairie, whereas colonies within mixed-grass prairie are more isolated. At a broad scale, we observed isolation-by-distance among colonies and great influence of grassland productivity on genetic connectivity; however, neither distance nor landscape characteristics greatly explained observed genetic differentiation among colonies separated by < 50 km. Last, we investigated whether landscape features could predict disease transmission patterns of sylvatic plague among colonies in short-grass prairie and found evidence that pastures act as corridors for plague transmission. Our results indicate that black-tailed prairie dogs are more resilient to habitat loss and fragmentation than other obligate grassland species and likely capable of transmitting sylvatic plague over long distances. Taken together, these studies illustrate how a multi-scale approach can reveal complexities of dispersal dynamics that would otherwise remain undetected.
Keywords: Movement ecology; Wildlife conservation; Black-tailed prairie dog; Ecology (0329); Wildlife Conservation (0284)